DAMPAK PERALIHAN FUNGSI KAWASAN HUTAN TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT (Studi Kasus: Kampung Lembur Pasir, Desa Ginanjar, Kecamatan Ciambar, Kabupaten Sukabumi, Jawa Barat) - Pratama, Aldo; Panjaitan, Poltak BP; Rusli, Abdul Rahman (Universitas Nusa Bangsa, 2015)
Change region switch the function of limited production forest area of the reserve has implications for the shape of people's activities in the region are limited. This study aims to determine the impact of the transition Perhutani office production forests into conservation forest area of the National Park on the socioeconomic conditions of rural communities around the area hutan. Metode research is a case study where data collection is done by using questionnaires and in-depth interviews and analysis of descriptive data. The results showed the impact of transfer of forest land to the socio-economic conditions of rural communities around the forest area, the social aspects of a decline in the number of pengarap land and increasing types of livelihood (of 6 types to 13 types of livelihood) and from the economic aspect, noticeable decrease in the use of firewood by the head of each family as well as a decline in revenue on each head of family who make their livelihood as this penggarap. Implications for the various issues that arise in the community where it takes an intensive development program.